DYNAMICS OF IRIG IN TREATMENT OF HEART TRANSPLANT REJECTIONS - A. O. Shevchenko; I. Yu. Tyunyaeva; A. A. Nasyrova; N. P. Mozheiko; S. V. Gautier (Вестник трансплантологии и искусственных органов, 2015)
In cardiac recipients non-invasive monitoring will identify the risk of acute rejection, as well as reduce the number of routine biopsies. The relation between the development of the transplanted heart rejection and the change of elastic properties of common carotid artery has been proved. Aim: to analyze dynamics of iRIG in treatment of graft rejection in heart recipients.Materials and methods. 59 heart recipients were examined: 21 patients (pts)without rejection, 20 pts – with rejection after 1st biopsy, 15 pts – with rejection after 1st and 2 biopsies, 3 pts – with persistent rejection after all biopsies. iRIG was estimated using empirical equation.Results. Dynamics of iRIG in pts. without rejection according to all biopsies over time was not signifi cantly changed 6280 ± 2143, 6083 ± 2388, 6362 ± 1984 and 6188 ± 3012 cm/sec2 (p = 0.11, p = 0.13, p = 0.17 between the 1st and 2nd, 2nd and 3rd, 3rd and 4th values, respectively). In pts. with rejection iRIG decreased during treatment, but was signifi cantly higher even after successful treatment. In patients with persistent rejection iRIG did not decrease and tended to increase (17 459 ± 9702 cm/sec2 on the results of the 1st biopsy to 21 305 ± 10 448 cm/sec2 on the results of the 4th biopsy).Conclusions. In patients with heart transplant iRIG does not change signifi cantly with the time after transplantation. iRIG increases in all types of rejection, followed by its decrease in the course of therapy; in patients with persistent rejection iRIG remains high. Evaluation of iRIG can be used for non-invasive monitoring of patients after heart transplantations (HTx) and to identify patients at high risk of transplant rejection.